ANALISIS NILAI COMPUTED TOMOGRAPHY DOSE INDEX VOLUME (CTDIvol) DAN DOSE LENGTH PRODUCT (DLP) PADA PEMERIKSAAN MSCT KEPALA - Shakira Alwi.; Ildsa Maulidya Marathus Nasokha; Ike Ade Nur Liscyaningsih; Arifin Musthafa (Bajang Institute, 2025)
Background: MSCT (Multislice Computed Tomography) produces higher radiation doses compared to other imaging modalities. The radiation dose delivered to patients is measured using two main parameters: the Computed Tomography Dose Index Volume (CTDIvol) and the Dose Length Product (DLP). To protect patients from excessive radiation exposure, BAPETEN (Nuclear Energy Regulatory Agency) monitors and enforces optimization measures through the Diagnostic Reference Level (DRL). This study aims to determine the level of radiation dose received by patients during non-contrast head MSCT examinations. Methods: A mixed-methods approach was used, including observation, interviews, documentation, and literature review. Research instruments comprised interview guides, a smartphone camera for documentation, and writing materials. The study subjects included 30 patients and one medical physicist, while the object of study was the monitor console of a Siemens 128-slice CT scanner used for patient data collection. Data analysis was performed using SPSS with the Shapiro-Wilk test for normality, followed by a one-sample t-test at a 95% confidence level to test the hypothesis. Results: The mean CTDIvol was 49.58 ± 0.04 mGy (range 49.5–49.6), and the mean DLP was 1,024 ± 257.28 mGy·cm (range 144–1,418). These values correspond to 82.63% of the CTDIvol limit and 80.31% of the DLP limit based on the national DRL (60 mGy; 1,275 mGy·cm). Variations in DLP among patients were due to differences in scan coverage length and repeated scans caused by patient movement, particularly in post-traffic accident cases with decreased consciousness. The one-sample ttest indicated a significant difference compared to the national DRL values (p < 0.05). Conclusion: Non-contrast head MSCT examinations at RSUD (Regional General Hospital) dr. Soehadi Prijonegoro Sragen comply with radiation protection optimization principles. The CTDIvol and DLP values obtained were below the national DRL limits set by BAPETEN, indicating that the scanning protocol is safe. Regular dose evaluation and the use of immobilization devices for uncooperative patients are recommended to minimize dose variability.